CITRAAN DALAM KUMPULAN PUISI ANAK PADA MAJALAH BOBO EDISI TANGGAL 20 JANUARI 2005 - Yunika Afryaningsih; Muhammad Aqmal Nurcahyo (Balai Bahasa Kalimantan Barat, 2018)
This research aims to describe an imagery of children’s poems collection from Bobo Magazine on January 20th 2015 edition. The research problem is about the types of imagery that contained in six children's poems, namely (1) Selamat Jalan, Cut, (2) Duka Aceh, (3) Aceh (Puisi Buat Anak Bangsa), (4) Ngarai Sianok, (5) Raporku, dan (6) Bencana di NAD. The types of imagery that will be examined in this research include (1) visual imagery, (2) auditory imagery, (3) tactile/thermal imagery, (4) smell imagery, (5) taste imagery, (6) movement imagery/kinaesthetic, and (7) feeling imagery. This research is a qualitative research with non-interactive qualitative method using an analytical approach. The results showed that not all types of imagery were contained in children's poems collection from Bobo Magazine on January 20th 2015 edition. Based on the results, it can be concluded that in one childrens’s poem can have two to five types of imagery.